The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1097/00005373-199611000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Volume Control and Pressure Control Ventilation

Abstract: Both pressure control ventilation and volume control ventilation with a decelerating flow waveform provided better oxygenation at a lower peak inspiratory pressure and higher mean airway pressure compared to volume control ventilation with a square flow waveform. The results of our study suggest that the reported advantages of pressure control ventilation over volume control ventilation with a square flow waveform can be accomplished with volume control ventilation with a decelerating flow waveform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 27 publications
7
57
0
1
Order By: Relevance
“…Comparison of volume control and pressure control ventilation using a tidal volume of 10 ml/kg, respiratory frequency to maintain a pH >7.30 and PaCO 2 <50 mmHg, and positive end-expiratory pressure, (PEEP) set to maintain PaO 2 > 70 mmHg or SaO 2 > 93% with an FiO 2 ≤0.50 was done by Davis K Jr et al and they concluded that both pressure controlled ventilation and volume controlled ventilation with a decelerating flow waveform provided better oxygenation at a lower peak inspiratory pressure and higher mean airway pressure compared to volume controlled ventilation with a square flow waveform. 15 The results were similar to our study with better oxygenation and lower peak inspiratoy pressures in pressure controlled ventilation than volume controlled ventilation. In a study on laparoscopic gastric banding surgeries for obesity by Cadi P et al, pressure controlled ventilation improved oxygenation as compared to volume controlled in morbidly obese patients.…”
Section: Resultssupporting
confidence: 89%
“…Comparison of volume control and pressure control ventilation using a tidal volume of 10 ml/kg, respiratory frequency to maintain a pH >7.30 and PaCO 2 <50 mmHg, and positive end-expiratory pressure, (PEEP) set to maintain PaO 2 > 70 mmHg or SaO 2 > 93% with an FiO 2 ≤0.50 was done by Davis K Jr et al and they concluded that both pressure controlled ventilation and volume controlled ventilation with a decelerating flow waveform provided better oxygenation at a lower peak inspiratory pressure and higher mean airway pressure compared to volume controlled ventilation with a square flow waveform. 15 The results were similar to our study with better oxygenation and lower peak inspiratoy pressures in pressure controlled ventilation than volume controlled ventilation. In a study on laparoscopic gastric banding surgeries for obesity by Cadi P et al, pressure controlled ventilation improved oxygenation as compared to volume controlled in morbidly obese patients.…”
Section: Resultssupporting
confidence: 89%
“…For the same V T , the same inspiratory time, and a descending ramp of flow with VCV, the differences in P aO 2 between PCV and VCV are trivial. 22 Experimental models of ALI/ARDS suggest that the high initial flow that occurs with PCV might be injurious rather than lung-protective. [23][24][25] Whether synchrony is better with PCV than VCV is also debatable.…”
Section: Pressure Controlled Versus Volume Controlled Ventilationmentioning
confidence: 99%
“…They found that PCV and VCV with a decelerating waveform lead to a lower PIP yet also to a higher mean airway pressure when compared with VCV with a square waveform. 19 A decelerating flow pattern (as is generated in PCV mode) is met with less flow resistance than the constant flow pattern of VCV, meaning that less airway pressure is generated and PIP is lower; however the decelerating pattern does tend to lead to higher mean airway pressures. 20 Unfortunately in our study we had no facility for measuring the mean airway pressure, so it is possible that despite generating a higher PIP, VCV may have produced equal or lower mean airway pressures.…”
Section: Discussionmentioning
confidence: 99%